Emissions reduction and deposits characteristics during cofiring of high shares of torrefied biomass in a 500 kW pulverized coal furnace. (15th September 2015) - Ndibe, Collins; Grathwohl, Simon; Paneru, Manoj; Maier, Jörg; Scheffknecht, Günter
Highlights: Full conversion of 500 kW pulverized coal rig to 100% torrefied biomass firing. Torrefied biomass combustion slower, may lead to higher gas exit temperatures. Cofiring at 50% thermal share reduces SOX and NOX substantially. Air-staging will reduce NOX during (co)firing of torrefied biomass even further. Smart biomass–coal blends will ameliorate operational issues such as slagging. Abstract: Combustion tests have been performed in a 500 kW pulverized coal furnace in order to investigate the cofiring characteristics of torrefied spruce and bituminous coal (El Cerrejon coal from Colombia). Monocombustion test cases for the coal and torrefied spruce were also performed for a comparative evaluation. Measurements performed include burn-out, gas temperature profiles and emissions characteristics (CO, NOX, SO2 and HCl). Combustion behavior was evaluated for all cases via measurement of the spatial distribution of oxygen across the flame and at the active combustion zones within the furnace. The impact of air staging on NOX reduction was investigated at two different primary or burner stoichiometric ratios for all fuels, while operational issues such as deposit formation and characteristics were also evaluated. The experimental study demonstrates the operational feasibility of cofiring at higher shares while also showing that emissions such as NOX and SOX can be reduced just by cofiring. Air-staging will even further reduce NOX emissions while smart fuel mixing will ameliorate operational issues related to ash characteristics such as slagging.